Public views of coronavirus science and scientists: findings from a cross-sectional survey [version 2; peer review: 1 approved, 2 approved with reservations] - Tim J. Peters; Michelle L. Taylor; Rachael Gooberman-Hill; Lucy Yardley; Ulrika Maude; Jo Stubbs; Richard Huxtable (Wellcome Open Research)
Background Throughout the coronavirus pandemic, references to scientific findings have permeated public-facing communications. Understanding how members of the public view science, scientists and scientific uncertainty should enhance approaches to communication and individuals’ decisions to engage with public health measures, including restrictions and vaccination programmes. This article provides descriptive statistics regarding public views and their univariable associations with key variables: age, gender, ethnicity, keyworker status, shielding status, caring responsibilities, and coronavirus exposure. Methods A survey was conducted on our behalf by YouGov in November 2020. The survey asked about: level of public trust in scientists and scientific information; changes in trust between March and November 2020; views about communication of scientific uncertainty; confidence in the accuracy of scientific findings; and views about whether public information accurately represents coronavirus science. Results The sample comprised 2,025 individuals in England; 40.5% were ≥55 years old, 51.1% were female; 12.3% identified as members of an ethnic minority/mixed ethnicity. Trust was highest among older respondents and those who identified as of white ethnicity. The concurrent (November 2020) levels of reported trust in scientific information about coronavirus were generally lower than those reported retrospectively for the pandemic’s start (March 2020). There was higher trust and positivity about science among people who had been shielding and among those who had not contracted coronavirus. Around half of respondents did not think that the uncertainty in science was conveyed much or at all, most were confident in the accuracy of coronavirus science, and around half thought that public information was a true representation of the science. Conclusions Our study indicates that there is room to improve trust and communication in science. As well as multivariable analyses to explore interrelationships, further research could examine reasons behind change in trust over time and any patterns due to age, ethnicity, and shielding status.